(untitled) (Research, Society and Development, 2020)
Studying the drying kinetics allows describing the process by mathematical models and obtaining information that helps to understand the phenomenon in question. Considering that watermelon (Citrullus lanatus) seeds have high moisture content and need to be subjected to drying, the objective was to select the model that best represents the drying behavior of watermelon seeds and determine the diffusion coefficient, activation energy and drying rate of these seeds at different temperatures. The seeds were dried in an experimental dryer at temperatures of 40, 45, 50, 55 and 60 °C, with air velocity of 0.8 m s-1, in four replicates. The models were fitted with non-linear regression analysis using the Gauss-Newton method. It was concluded that the models that best represent the drying kinetics of watermelon seeds are Approximation of Diffusion for temperatures of 40, 50 and 55 °C and Page for 55 and 60 °C. The highest drying rates are observed at the highest temperatures. The diffusion coefficients presented magnitude of 7.69684×10-10 and 1.27585×10-9 for the range from 40 to 60 °C, and the activation energy was 12.2641 kJ mol-1.